Seeing the elephant - Marber, Peter (John Wiley & Sons, 2009)
Seeing the Elephant demystifies globalization, and analyzes the megatrends and interconnections of the 21st century. With bold suggestions on how America reassert its historic leadership in the new global arena, Seeing the Elephant should be required reading for policy makers, businessmen and informed citizens alike